2014
DOI: 10.1007/s10157-013-0921-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of galactose-deficient immunoglobulin (Ig) A1 and related immune complex are associated with disease activity of IgA nephropathy

Abstract: BackgroundThe primary abnormal manifestation in immunoglobulin A nephropathy (IgAN) is recurring bouts of hematuria with or without proteinuria. Although immunohistochemical analysis of renal biopsy tissue remains the gold standard not only for diagnosis but also for evaluating the activity of IgAN, new sensitive and reasonably specific noninvasive tests are emerging to guide therapeutic strategy applicable to all stages of IgAN. The present study examined serum levels of galactose-deficient IgA1 (Gd-IgA1) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 34 publications
1
59
0
Order By: Relevance
“…Cases with IgAN who showed significant decreases in serum Gd-IgA1 levels after tonsillectomy achieved significantly better improvement in hematuria [29]. Moreover, serum levels of Gd-IgA1 and IgA-IgG IC were examined before and after tonsillectomy with steroid pulse therapy [48]. Cross-sectional analysis revealed that the amounts of hematuria and proteinuria were significantly associated with serum levels of Gd-IgA1 and levels of IgA-IgG immune complexes [48].…”
Section: Gd-iga1 and Its Related Immune Complexes As Biomarkers For Dmentioning
confidence: 99%
“…Cases with IgAN who showed significant decreases in serum Gd-IgA1 levels after tonsillectomy achieved significantly better improvement in hematuria [29]. Moreover, serum levels of Gd-IgA1 and IgA-IgG IC were examined before and after tonsillectomy with steroid pulse therapy [48]. Cross-sectional analysis revealed that the amounts of hematuria and proteinuria were significantly associated with serum levels of Gd-IgA1 and levels of IgA-IgG immune complexes [48].…”
Section: Gd-iga1 and Its Related Immune Complexes As Biomarkers For Dmentioning
confidence: 99%
“…10 In IgAN, it is unclear whether IgA1-containing circulating immune complexes have complement elements. [77][78][79][80] Nevertheless, elevated serum concentrations of C3-derived products in patients with IgAN suggest a soluble-phase activation of the alternative pathway. 28 Proteomic analyses of patients' circulating immune complexes and complexes formed in vitro from Gd-IgA1 and antiglycan IgG revealed the presence of C3.…”
Section: Where Complement Is Activated: From Soluble Circulating Immumentioning
confidence: 99%
“…[15][16][17] IgAN usually has a poor prognosis, with about 50% of patients progressing to end-stage renal disease within 30 years despite treatment. 18 Mesangial deposition of IgA has been considered to be the initiating event in the pathogenesis of IgAN; however, the origin of the increased IgA remains unclear.…”
Section: Discussionmentioning
confidence: 99%